“Alcanzar a Dios sin Dios”. La relación entre fenomenología y teología en Edmund Husserl y Jean-Luc Marion - Pizzi, Matías Ignacio (2020)
“‘Reaching God without God’. The relationship between phenomenology and theology in Edmund Husserl and Jean-Luc Marion”. By assuming that there is a fruitful historical relationship between theology and phenomenology, this work aims to point out the specificity and novelty of current French phenomenology. This will be achieved by highlighting the difference between the theological model that the latter draws on from the type of theology with which it dialogues historical phenomenology. First, we will address the relationship between phenomenology and theology offered by Edmund Husserl, supporting the presence of a positive theology, since God is named under such terms as ??????????, “idea” (Idee) and “absolute substance” (absolute Substanz). Secondly, we will show the link between phenomenology and theology proposed by Jean-Luc Marion from his interpretation of Dionysius Areopagite’s thought as “pragmatic theology of absence” (pragmatique théologie de l’absence), as it appears in De surcroît (2001). Finally, we will establish a dialogue between both proposals. We will argue that a fundamental difference can be found between them. On the one hand, Husserl appeals to a positive theology, since God breaks into the horizon of the Grenzprobleme of phenomenology. On the other hand, we will argue that an appeal to mystical theology can be found in Marion as a search for a language that allows the expression of excess.